BLOOD GROUP RELATIONSHIP WITH CORONARY HEART DISEASE - Samuel Ginting; Pitriani .; Juni Mariati Simarmata; Chaidir Saputra Harahap (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2021)
Coronary heart disease is a heart disease caused by narrowing of the coronary arteries, starting from the occurrence of atherosclerosis (arterial stiffness) or the accumulation of fat or plaque (plague) on the walls of the coronary arteries, either accompanied by clinical symptoms or without symptoms. Coronary heart disease (CHD) is widely reported in developed countries. The incidence of CHD in European men was recorded by WHO in 1976 as 2-14 per 1000 population and CHD is mostly found in Finland. In developing countries, the prevalence of CHD is generally rare. In South Africa in 1970 the death rate from CHD was 0.05 per 1000 black population and 1.9 per 1000 white population. In Ujung Pandang, the average treatment for CHD is 0.3 per 1000 patients. The type of research used is a quantitative study with a descriptive correlation research design, which is a study or study that describes the relationship between two variables in a situation or group of subjects. This is done to see the relationship between one variable with another variable. This study aims to see the relationship between blood type and the incidence of coronary heart disease in the CVCU room at Haji Adam Malik General Hospital Medan in 2010. The population of this study was 11 people using incidental sampling. From the statistical test using the Chi-Square test analysis, it was found that p (value) = 0.012 where p (value) < 0.05. So the results of these tests found a very close and real relationship between the relationship between blood type and the incidence of coronary heart disease. The results of this study can be used as information and increase knowledge for nursing services in hospitals about the relationship between blood type and the incidence of coronary heart disease.